2008
DOI: 10.4049/jimmunol.180.3.1678
|View full text |Cite
|
Sign up to set email alerts
|

Two Novel NKG2D Ligands of the Mouse H60 Family with Differential Expression Patterns and Binding Affinities to NKG2D

Abstract: H60, originally described as a dominant minor histocompatibility Ag, is an MHC class I-like molecule that serves as a ligand for the NKG2D receptor. In the present study, we identified two novel mouse chromosome 10-encoded NKG2D ligands structurally resembling H60. These ligands, which we named H60b and H60c, encode MHC class I-like molecules with two extracellular domains. Whereas H60b has a transmembrane region, H60c is a GPI-anchored protein. Recombinant soluble H60b and H60c proteins bound to NKG2D with af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
109
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(119 citation statements)
references
References 60 publications
10
109
0
Order By: Relevance
“…We will follow the ULBP nomenclature from this point. In mouse, NKG2D ligands comprise three members of the H60 family, five members of the Rae1 (retinoic acid early inducible transcript-1) family, and Mult-1 (murine ULBP-like transcript) [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We will follow the ULBP nomenclature from this point. In mouse, NKG2D ligands comprise three members of the H60 family, five members of the Rae1 (retinoic acid early inducible transcript-1) family, and Mult-1 (murine ULBP-like transcript) [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…We will follow the ULBP nomenclature from this point. In mouse, NKG2D ligands comprise three members of the H60 family, five members of the Rae1 (retinoic acid early inducible transcript-1) family, and Mult-1 (murine ULBP-like transcript) [14][15][16][17].According to the initial models of NKG2D function, its ligands were thought to be largely absent from healthy cells, but their expression could be induced on viral infection and on tumourigenesis [1]. Ectopic expression of NKG2D ligand leads to anticancer immune responses to transplanted tumours in mice, and the NKG2D knockout mouse has an increased susceptibility to certain types of cancer [18][19][20].…”
mentioning
confidence: 99%
“…The identified mouse NKG2D ligands include family members of: the MHC I-related family members of retinoic acid early transcript RAE-1(α, β, γ, δ, and ε) and H60 (a, b, c), and the murine ULBP-like transcript 1 (MULT1) (Cerwenka et al, 2000;Diefenbach et al, 2003;O'Callaghan et al, 2001;Takada et al, 2008). All of these ligands only have the MHC class I-like α1 and α2 extracelluar domains.…”
Section: Nkg2d Ligands In Micementioning
confidence: 99%
“…H60a, the first ligand of the family was initially identified as a minor histocompatibility antigen by immunizing C57BL⁄6 mice with MHC-identical BALB.B cells (Malarkannan et al, 1998). Two novel members of H60 family were identified, and named as H60b and H60c (Takada et al, 2008). MULT1 is the unique member of the ULBP-like family of mouse NKG2D ligands and was found by database searching for mouse sequences with similarities to human ULBP (Carayannopoulos et al, 2002).…”
Section: Nkg2d Ligands In Micementioning
confidence: 99%
“…These data suggested that Mult1 cell surface expression is controlled posttranscriptionally, either at the translational or protein level. To test for protein level regulation, the open reading frames of Mult1 or of a distantly related NKG2D ligand, H60c ( 18 ), were N-terminally FLAG tagged and cloned into a retroviral expression vector in the absence of their untranslated regions, which might contain cis-acting elements that regulate mRNA stability. The vector used for this analysis encoded a downstream IRES-GFP cassette, such that GFP expression could be used as a marker to indicate that cells had been successfully transduced and expressed the bicistronic Mult1-GFP mRNA.…”
Section: Ectopically Expressed Mult1 Protein Is Ineffi Ciently Displamentioning
confidence: 99%